can anyone see some way of getting to yy'=x
from
integral of y^2 from -a to a (dx) = 1 ?
p.s. i am trying d/dx {integral of y^2 from -a to a (dx)} =0, but find my self lost!
thanks
does the following make sense?
d/dx {integral of y^2 from -a to a (dx)} =0
=>
integral of d(y^2)/dx from -a to a (dx) =0
=>
integral of 2yy' from -a to a (dx) =0
=>
integral of yy' from -a to a (dx) =0
=>
integral of yy' from -a to a (dx) =integral of x from -a to a = 0
=>
yy'=x
??
okay, now suppose that can be derived from Then it means we have two facts that and From my last reply, we get the function must satisfy However, it is wrong. For example, let for all which also satisfies A contradiction!
pepsi, actually, you should have known that is an integral equality, while is a differential equation. pay attention to theire solution sets of functions, respectively!!!